2017
DOI: 10.1017/s1041610217000631
|View full text |Cite
|
Sign up to set email alerts
|

The lived neighborhood: understanding how people with dementia engage with their local environment

Abstract: Background:In this paper, we report progress on “Neighborhoods: our people, our places” an international study about how people living with dementia interact with their neighborhoods. The ideas of social health and citizenship are drawn upon to contextualize the data and make a case for recognizing and understanding the strengths and agency of people with dementia. In particular, we address the lived experience of the environment as a route to better understanding the capabilities, capacities, and competencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 39 publications
8
100
0
Order By: Relevance
“…For instance, the findings indicated that a 'neighbourhood' was a place where the couples lived, but more significantly was a product of their connections with 'people' and 'places' and their access to 'resources', coupled with their interpretation of 'being in place'. Our findings also endorse the position of the 'lived' neighbourhood (Ward et al 2018) where people living with dementia can use their potential and capabilities to offset the limitation they encounter. In addition, the three themes draw attention to participants' inside views of the world outside through illustrating their feelings of belonging and connection to their neighbourhood, thereby enriching and advancing the concept of 'neighbourhood' being a lived place within a flexible and fluid geographical boundary.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…For instance, the findings indicated that a 'neighbourhood' was a place where the couples lived, but more significantly was a product of their connections with 'people' and 'places' and their access to 'resources', coupled with their interpretation of 'being in place'. Our findings also endorse the position of the 'lived' neighbourhood (Ward et al 2018) where people living with dementia can use their potential and capabilities to offset the limitation they encounter. In addition, the three themes draw attention to participants' inside views of the world outside through illustrating their feelings of belonging and connection to their neighbourhood, thereby enriching and advancing the concept of 'neighbourhood' being a lived place within a flexible and fluid geographical boundary.…”
Section: Discussionsupporting
confidence: 74%
“…It is this conflicting position that has stimulated interest in a 'person-in-environment' approach to dementia studies in order to better understand the complex relationships and inter-relationships that are happening in such everyday settings (Blackman 2006;Duggan et al 2008;Huber et al 2011;McGovern 2016;Tranvåg, Petersen and Nåden 2015;Ward et al 2018;Wiersma and Denton 2016). Generally speaking, transforming spaces into meaningful places derives from using spaces over time, so forming patterns of familiarity and comfort, which contribute towards the development of an emotional attachment and a sense of ownership (Rowles and Bernard 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wiles et al 2012;Gillsjö et al 2011;Soilemezi et al 2017;Ward et al 2017;Keady et al 2012;Keady et al 2014;Nygård, 2004 Comfort/safety inside home Comfort/safety outside home Being able to stay in familiar environments. Importance of facilitating daily activities and chores to promote independence and activity inside the home and in the neighborhood.…”
Section: Methodsmentioning
confidence: 99%
“…Importance of facilitating daily activities and chores to promote independence and activity inside the home and in the neighborhood. Tanner et al 2008;Torrington, 2009;Werthon & Monk, 2008;Soilemezi et al 2017;Mitchell & Burton, 2010;Keady et al 2012;Ward et al 2017;Keady et al 2014 Physical wellbeing Physical activity as a source of doing things together as a couple and to promote healthy aging, cognitive function and physical wellbeing.…”
Section: Methodsmentioning
confidence: 99%